Pengaruh Volatilitas Ekuitas dan Leverage terhadap Risiko Investasi - Mohamad Chaidir; Grace Yulianti; Benardi Benardi (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
This study aims to analyze the impact of equity volatility and leverage on investment risk, focusing on the relationship between debt overhang and equity option value. Through a qualitative literature review, this research reveals that equity volatility plays a role in reducing companies' incentives to invest, especially amid market uncertainty. Meanwhile, high leverage can worsen a company's inability to invest due to the heavy debt burden. The phenomenon of debt overhang causes companies to be reluctant to invest because the benefits generated from such investments are primarily enjoyed by creditors. This study provides valuable insights into the interaction between equity volatility, leverage, and debt overhang in corporate investment decision-making, as well as the importance of effective financial risk management.